Development of a multiblock procedure for automated generation of two-dimensional quadrilateral meshes of gear drives. (January 2020) - Roda-Casanova, Victor; Sanchez-Marin, Francisco
Highlights: A new meshing procedure is developed to mesh planar sections of gear drives. The new procedure is completed with two mesh quality enhancement techniques. Different gear geometries have been meshed under several meshing conditions. Resulting meshes are compared to the meshes obtained from traditional procedures. Unlike other approaches, this procedure is capable to perform local mesh refinement. Graphical abstract: Abstract: This article describes a new multiblock procedure for automated generation of two-dimensional quadrilateral meshes of gear drives. The typical steps of the multiblock schemes have been investigated in depth to obtain a fast and simple way to mesh planar sections of gear teeth, allowing local mesh refinement and minimizing the appearance of distorted elements in the mesh. The proposed procedure is completed with two different mesh quality enhancement techniques. One of them is applied before the mesh is generated, and reduces the distortion of the mesh without increasing the computational time of the meshing process. The other one is applied once the mesh is generated, and reduces the distortion of the elements by means of a mesh smoothing method. The performance of the proposed procedure has been illustrated with several numerical examples, which demonstrate its ability to mesh different gear geometries under several meshing boundary conditions.